Relationship between aneurysm occlusion and flow diverting device oversizing in a rabbit model. (11th November 2014) - Hodis, Simona; Ding, Yong-Hong; Dai, Daying; Lingineni, Ravi; Mut, Fernando; Cebral, Juan; Kallmes, David; Kadirvel, Ramanathan
Abstract : Background and purpose: Implanted, actual flow diverter pore density is thought to be strongly influenced by proper matching between the device size and parent artery diameter. The objective of this study was to characterize the correlation between device sizing, metal coverage, and the resultant occlusion of aneurysms following flow diverter treatment in a rabbit model. Methods: Rabbit saccular aneurysms were treated with flow diverters (iso-sized to proximal parent artery, 0.5 mm oversized, or 1.0 mm oversized, respectively, n=6 for each group). Eight weeks after implantation, the angiographic degree of aneurysm occlusion was graded (complete, near-complete, or incomplete). The ostium of the explanted aneurysm covered with the flow diverter struts was photographed. Based on gross anatomic findings, the metal coverage and pore density at the ostium of the aneurysm were calculated and correlated with the degree of aneurysm occlusion. Results: Angiographic results showed there were no statistically significant differences in aneurysm geometry and occlusion among groups. The mean parent artery diameter to flow diverter diameter ratio was higher in the 1.0 mm oversized group than in the other groups. Neither the percentage metal coverage nor the pore density showed statistically significant differences among groups. Aneurysm occlusion was inversely correlated with the ostium diameter, irrespective of the size of the device implanted. Conclusions: Device sizing alone does not predict resultant pore density or metal coverage following flow diverter implantation in the rabbit aneurysm model. Aneurysm occlusion was not impacted by either metal coverage or pore density, but was inversely correlated with the diameter of the ostium.